Environmental footprints of livestock production systems in Northern Laos: A case study of Nonghet district - Dao Thu, Hang Thi; Notenbaert, An; Philp, Joshua; Otieno, Mary Atieno (International Center for Tropical Agriculture, 2025)
In the frame of the MFS initiative and ASEAN-CGIAR program, this study aims to fill critical knowledge gaps by quantifying the environmental impacts of different livestock production systems, using the CLEANED tool, in Nonghet district, Xiengkhouang Province. By employing a typology-based approach, the research seeks to classify farms into distinct categories, analyze their environmental footprints, and identify high-risk areas for degradation. The study’s ultimate goal is to provide actionable recommendations for mitigating environmental impacts while improving productivity and livelihoods. By focusing on these objectives, this research aligns with national and regional development goals, contributing to the sustainable intensification of agriculture in Laos. The findings will serve as a valuable resource for policymakers, and local communities in their efforts to enhance the sustainability of livestock production systems.